Behavioural adaptation of the rice leaf folder Cnaphalocrocis medinalis to short-term heat stress. (July 2017) - Bodlah, Muhammad Adnan; Gu, Ling-Ling; Tan, Ye; Liu, Xiang-Dong
Graphical abstract: Highlights: The rice leaf folder is a serious migratory pest in rice fields. Shelter-making velocity of larvae is decreased during or after heat exposure. Larvae and adults can choose microhabitat to cope with heat stress. Abstract: Under ongoing climate warming, both the degree and number of high-temperature events in summer may increase, and behavioural adaptation is an important ecological strategy employed by insects to cope with such events. The rice leaf folder, Cnaphalocrocis medinalis Güenée, is a serious insect pest of rice fields in summer. Population outbreaks have become more frequent in the last ten years. In addition to adult migration, rice leaf folders are thought to have other thermal adaptations. Therefore, the behaviours of larval and adult rice leaf folders, such as leaf folding (making shelter) and habitat selection for pupae and eggs, were observed on rice plants under heat stress. The results showed that larval shelter-making velocities significantly decreased during or after four hours of heat exposure, and shelter size decreased as the temperature increased. Larvae preferred to pupate on young rice leaves at 27 °C and middle-aged leaves at 30 °C, but they strongly preferred older leaves when reared at 34 °C. Female moths generally preferred to oviposit on the top of young leaves, but they preferred the middle and lower leaves for egg deposition when exposed to 36 and 40 °C, respectively. Furthermore, more eggs were distributed on the lower surfaces of rice leaves with an increase in heat stress. These behavioural responses of rice leaf folders to heat stress indicate that this pest has great potential to adapt to high temperatures; therefore, the possibility of a population outbreak will remain high despite global warming.